The Performance of A Diesel Engine Fueled With Diesel Oil, Biodiesel and Preheated Coconut Oil - Tuan Anh Hoang; Vang Van Le (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Fossil fuel crisis and depletion, environmental pollution and ever-increase in vehicle and transportation means have renewed the scientist’s interest in the world in order to look for potential alternative fuels, which are attractive such as biodiesel, bioethanol, DME and vegetable oils. Inedible vegetable oils such as coconut oil, Jatropha oil, linseed oil or animal fat are full of potential for using directly or manufacturing biodiesel. This work is carried out in order to study the four stroke diesel engine D240 performance characteristics fueled with preheated pure coconut oil (PCO), Jatropha oil methyl ester (JOME) and compare with diesel oil (DO). The test diesel engine performance such as power (Ne), torque (Me), specific fuel consumption (ge) and thermal efficiency (ηe) is determined, calculated and evaluated while using JOME, preheated PCO and compared to DO. The results show that, power (Ne), torque (Me) and thermal efficiency (ηe) while engine is fueled with JOME and PCO are lower, otherwise specific fuel consumption (ge) is higher than those of diesel fuel, the test engine performance are gained the best for JOME and PCO100.Article History: Received Dec 9, 2016; Received in revised form January 28, 2017; Accepted February 4, 2017; Available onlineHow to Cite This Article: Hoang, T.A and Le,V. V. (2017). The Performance of A Diesel Engine Fueled With Diesel Oil, Biodiesel and Preheated Coconut Oil. International Journal of Renewable Energy Development, 6(1), 1-7.http://dx.doi.org/10.14710/ijred.6.1.1-7